2021
DOI: 10.1002/aur.2532
|View full text |Cite
|
Sign up to set email alerts
|

Social attention as a cross‐cultural transdiagnostic neurodevelopmental risk marker

Abstract: The primary objectives of this study were to evaluate the structure and age‐related stability of social attention in English and Arabic‐speaking youth and to compare social attention between children with autism spectrum disorder (ASD), other developmental disabilities (DD), and typically‐developing controls. Eye‐tracking data were collected from US (N = 270) and Qatari (N = 242) youth ages 1–17, including children evaluated for possible ASD. Participants viewed 44 stimuli from seven social paradigms. Fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 62 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…Further, processing of eye gaze may be as fundamental or more fundamental to social attention development than face processing per se [e.g., ( 134 , 136 )] and the development of social orienting and joint attention may share common neurodevelopmental and genetic substrates [e.g., ( 199 , 233 )]. A unified measurements model of social attention that combines measures of social orienting and joint attention may be more powerful way forward in research on social attention in ASD ( 118 , 119 ). However, a unified measurement model that allows for the direct comparison of data from joint attention and social orienting measures on the same samples of children in future research is still needed to truly examine the relations between these two types of social attention in the development of ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, processing of eye gaze may be as fundamental or more fundamental to social attention development than face processing per se [e.g., ( 134 , 136 )] and the development of social orienting and joint attention may share common neurodevelopmental and genetic substrates [e.g., ( 199 , 233 )]. A unified measurements model of social attention that combines measures of social orienting and joint attention may be more powerful way forward in research on social attention in ASD ( 118 , 119 ). However, a unified measurement model that allows for the direct comparison of data from joint attention and social orienting measures on the same samples of children in future research is still needed to truly examine the relations between these two types of social attention in the development of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…This level of reliability may be difficult to obtain with research that employs only one or the other social attention paradigm. However, a multivariate latent construct measurement model may be expected to improve reliability and power in social attention research on ASD ( 118 , 119 ). Attempts to utilize a multivariate, latent construct approach to social attention measurement have begun to appear in the literature ( 119 ), but much more research is needed to understand the utility of this approach.…”
Section: Toward a Unified Measurement Model Of Social Attentionmentioning
confidence: 99%
“…The limited number of girls in ASD group foiled our intention of analyzing gender differences within the ASD children. This task is especially relevant considering that previous research have found that older girls with ASD pay more social attention than boys (Frazier et al, 2021) and are more communicative (Wood‐Downie et al, 2021). In addition, gender differences have been found in social attention during the first year of life in girls than have an older sibling with ASD (Chawarska et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Eye tracking is a relatively new approach for rapidly and accurately characterizing attention in ASD 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 and holds promise as a screening and diagnostic tool. 31 , 33 Eye-tracking studies, however, have been largely restricted to the visual domain and have demonstrated reduced attention to social visual images in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…In a brain imaging study, toddlers with ASD who showed the lowest levels of attention to motherese speech also showed the lowest levels of neural functional activation in speech-processing regions and lower language abilities than toddlers who paid greater attention to motherese speech. 27 Eye tracking is a relatively new approach for rapidly and accurately characterizing attention in ASD [28][29][30][31][32][33][34][35][36][37] and holds promise as a screening and diagnostic tool. 31,33 Eye-tracking studies, however, have been largely restricted to the visual domain and have demonstrated reduced attention to social visual images in ASD.…”
Section: Introductionmentioning
confidence: 99%